Kompetensi Guru Pendidikan Agama Islam Dalam Pemanfaatan Teknologi untuk Pembelajaran Daring pada Masa Pandemik Covid-19 - Ibnu Hasyim; Idi Warsah; Muhammad Istan (JOEAI:Journal of Education and Instruction, 2021)
The purpose of this study was to determine the competence of Islamic Religious Education teachers in the use of technology for online learning during the Covid 19 pandemic at SMP N Muara Kulam, North Musi Rawas Regency. This research is a qualitative research, the subject consists of the principal, PAI teacher, vice principal of students, parents/guardians of students. The data were obtained by observation and interview techniques, the data were analyzed using the data reduction method, data display, and conclusion drawing/verification. The results of the study, found several problems in the application of online learning at SMP Negeri Muara Kulam while the most basic problems were the unavailability of adequate wifi and internet networks, lack of support from parents / guardians of students for online learning, so that the learning process became hampered. In conclusion, the application and use of technology for learning by PAI teachers at SMP Negeri Muara Kulam is considered ineffective and not feasible to apply, due to several obstacles found as a result of the research. This condition is our collective duty, both principals, PAI teachers and all stakeholders to jointly find solutions to these problems, for the sake of the interests and progress and development of Islamic Religious Education technology. Keywords: Teacher competence, PAI, Learning Technology